Canadian Cannabis: Orthodoxies of Exclusion and Access - McCann, Clayton (My University, 2023)
The dissertation that follows is the result of extended collaboration with, and co-labouring among women working in an illicit, value-added cannabis production facility, 400115335 BC, in the southeastern interior of British Columbia, Canada, in the lower Slocan Valley. An extended case study of the political economy leveraged against these workers ensues, which exposes the mechanisms depriving them of state provisions and protections normally afforded to Canadian citizens. Illegal firms employing unprotected workers, with the full consent of local and provincial authorities, represent the significant findings of this research. Further, the work engages in ethnographic content analysis to evaluate the intentional exclusion of illicit cannabis producers in the West Kootenay region, and in Canada more generally, from the approvals and licenses that would permit them to participate in legal markets. An examination of late capitalist financialisation is presented to illustrate that ex-politicians and law enforcement persons prioritised their personal access to cannabis production licenses and markets over that of a five decades-old, established industry, excluding hundreds of functioning production farms, opting instead to create cannabis production firms incapable of producing at scale, many of which either engaged, or continue to engage in malfeasant practices such as deployment of the deceptive IFRS accounting methodology, the over-compensation of corporate principals, and the “pump and dump” stock valuation scam, a form of insider trading.
ORTHODOXIES OF EXCLUSION AND ACCESS
Keywords: Cannabis; Legalisation